(untitled) (Revista Brasileira de Agroecologia, 2018)
The objective of this study was to verify the occurrence and use of medicinal herbs in families living in urban areas. The research was carried out in five cities in the "Planalto Serrano" region of Santa Catarina State, Brazil. The first family was indicated by the health department of the municipality and the following were indicated by the previous one, according to snowball methodology. Interviewees ranged from 39 to 78 years old, who cited 84 species of plants to treat 205 diseases. The herbs were collected from yard (50%), garden (20.2%), neighbors (14.5%), field (8.9%), or bought (6.4%). The using of medicinal herbs still persists in families living in urban areas of the south plateau of Santa Catarina State, Brazil. There is a predominance of females as maintainers and concentrated on people over 50 years.